Efeitos do plasma rico em plaquetas na expressão de metaloproteinases MMP-2 e MMP-9 no líquido sinovial de equinos com sinovite induzida - Peixoto, Andréia da Costa (2019)
The equine musculoskeletal system suffers contant overload, what increases its predispositon to injuries, particularly the development of joint diseases. Conventional anti-inflammatory treatments have both temporary and symptomatic effects, as well as unwanted side effects. Platelet Rich Plasma (PRP) has been studied as a regenerative cellular therapy for joint diseases as it aims the modulation of extracellular matrix degradation and regeneration (MEC) factors. Important degradation factors are the metalloproteinases (MMPs), especially MMP-2 (Matrix metalloproteinases type 2) and MMP-9 (Matrix metalloproteinases type 9) in equines. Therefore the aim of this dissertation is to review the elements involved in the arthropathies, and investigate the intra-articular effects of PRP on the MMP-2 and MMP- 9expression. Twelve healthy horses were divided into groups: Control and Treatment (CG and GT). Induction of synovitis was performed in all horses by means of lipopolysaccharide (LPS) injection into the left radiocarpal joint. GT was treated with a single intrasinovial PRP injection. PRP was obtained by double centrifugation method. The expression of MMP-2 and MMP-9 in the synovial fluid was determined by ELISA test. Density, pH, glucose, protein, red blood cells and nucleated cells were also determined. These analysis were done prior to and after induction of synovitis and six, 24 and 48 hours after PRP injection. Regarding MMPs expression, there was no difference between groups (p> 0.05), as well as in the evaluation of glucose, red blood cells and nucleated cells. However, density, pH and proteins were different in the comparison between the two groups at six hours post PRP treatment (p = 0.0057; p = 0.0233; p = 0.0152, respectively). In the experimental model of induced synovitis in horses, PRP seems to have an influence on MMP-2 levels, but not on MMP-9, although it was not statistically observed. In addition, it also influenced the physico-chemical and cytological aspects of LS.